2015
DOI: 10.1111/risa.12356
|View full text |Cite
|
Sign up to set email alerts
|

A Farm Transmission Model for Salmonella in Pigs, Applicable to E.U. Member States

Abstract: The burden of Salmonella entering pig slaughterhouses across the European Union is considered a primary food safety concern. To assist E.U. member states with the development of national control plans, we have developed a farm transmission model applicable to all member states. It is an individual-based stochastic susceptible-infected model that takes into account four different sources of infection of pigs (sows, feed, external contaminants such as rodents, and new stock) and various management practices link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
1
31
1
Order By: Relevance
“…(j,k), but in this case the variation between simulations is larger than the effect of altering the value. [0.25,0.5, 1,2,3,4,5,6,7,8,9,10,12,14] Halving the storage…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(j,k), but in this case the variation between simulations is larger than the effect of altering the value. [0.25,0.5, 1,2,3,4,5,6,7,8,9,10,12,14] Halving the storage…”
Section: Resultsmentioning
confidence: 99%
“…As stated previously, the exposure assessment modules are discussed in detail elsewhere. (4)(5)(6)(7) For clarity we provide a brief overview here. The Farm module describes the transmission of Salmonella infection between pigs on a farm.…”
Section: Exposure Assessment Modules: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are, therefore, promising but a much larger study, which takes in to account multi-variant effects, needs to be done before we can be more confident that pre-inoculation with S. Infantis 1326/28Ф r can inhibit or prevent shedding of S. Typhimurium in the immediate post-weaning period under conditions similar to those in the field. However, one study has suggested that the greatest risk factor for infecting piglets is the prevalence of Salmonella in the breeding herd and that the likelihood of transmission is high if the breeding herd prevalence is >10% (Hill et al 2015). It is therefore possible that oral inoculation with the candidate vaccine strain S. Infantis 1326/28Ф r could also be applied to the breeding herd to reduce Salmonella carriage in pregnant sows.…”
Section: Discussionmentioning
confidence: 99%
“…The third module ‘Food Production Exposure Assessment’ involved studying and properly running a ‘farm‐to‐consumption’ simulation to understand how the different basic processes of a quantitative microbiological risk assessment (QMRA) could be applied to modelling the variations in prevalence and concentration of a pathogen (Nauta, ). To this purpose, a QMRA was employed on ‘ Salmonella in Slaughter and Breeder Pigs’ developed for EFSA by a European Consortium led by APHA (Hill et al., ,b; Simons et al., ; Snary et al., ,b; Swart et al., ,b; Vigre et al., ,b). The model deals with four European countries and, as main output, it calculates the risk of human salmonellosis associated with the consumption of fresh pork cuts, minced meat and fermented sausage.…”
Section: Description Of Work Programmementioning
confidence: 99%